LB0002 Novel Injection Needle with Real-Time Detection of Synovial Fluid – Exploratory Clinical Study. (9th June 2015) - Parmanne, P.; Kankaanpää, E.; Mäki, S.; Kari, J.; Relas, H.; Tuompo, R.; Peltomaa, R.; Kronström, K.; Luosujärvi, R.
Abstract : Background: Intra-articular glucocorticoid injections are recommended for local treatment of synovitis regardless of the disease severity or the concurrent therapy [1]. However, the accurate placement of the puncture is challenging and if not succeeded it may impair clinical outcome or even lead to complications. The accuracy rate of non-guided injections varies around 30% - 80% [2, 3] which emphasizes the need for needle guidance. In addition to established methods (e.g. ultrasound), electrical tissue properties can be utilized for needle guidance [4]. Objectives: This study introduces a new real-time needle guidance method which utilizes bioimpedance spectroscopy (BIS) with standard 22G and 24G needles. In this exploratory clinical study the system parameters are tuned and performance tested. Methods: The measurement system (Injeq Ltd) consisted of a conventional injection needle together with a bioimpedance probe (BIP) stylet connected to the measurement device (as shown in Figure ). It performs bipolar BIS between the electrode at the tip of the stylet and the surrounding needle. Based on the BIS results, system classifies the tissue using mathematical model in real-time and beeps when synovial fluid is detected. Parameter tuning was performed during studies based on offline analysis. In this phase, 23 patients suffering from arthritis were injected to 31 joints by experienced rheumatologists. Success of the injection was verified by aspiration of synovial fluid, absence of resistance during injection and/or using ultrasound imaging for locating the needle. Results: The electrical properties of human synovial fluid differ significantly from surrounding tissues. Small and inflamed joints do not appear to contain pure well conducting synovial fluid, but they are still distinguishable from the surrounding tissues. This kind of new class, termed Complex, was included to the model after 10 injections. After the inclusion, the device correctly detected either Complex or Pure synovial fluid in 18 out of 21 injections. One joint was dry and device provided true negative result. Remaining two injections were false negative. Conclusions: BIP needle is a new, easy to use method for assisting placement of the needle during intra-articular injection. In this exploratory phase, synovial fluid detection functioned properly in 19/21 cases. Thus, BIP showed ability to provide needle guidance and the study will be continued to statistically significant phase. References: Beukelman T et al. 2011 American College of Rheumatology recommendations for the treatment of juvenile idiopathic arthritis: initiation and safety monitoring of therapeutic agents for the treatment of arthritis and systemic features. Arthritis Care & Research 63.4 (2011): 465-482. Balint PV et al. Ultrasound guided versus conventional joint and soft tissue fluid aspiration in rheumatology practice: a pilot study. J. Rheumatol. 29.10 (2002): 2209-2213. Pichler W et al. Frequency of successful intra-articular puncture of finger joints: influence of puncture position and physician experience. Rheumatology 47.10 (2008): 1503-1505. Kalvøy H et al. Impedance-based tissue discrimination for needle guidance. Physiological measurement 30.2 (2009): 129-140. Disclosure of Interest: P. Parmanne: None declared, E. Kankaanpää: None declared, S. Mäki Employee of: Injeq, J. Kari Employee of: Injeq, H. Relas: None declared, R. Tuompo: None declared, R. Peltomaa: None declared, K. Kronström Shareholder of: Injeq, Employee of: Injeq, R. Luosujärvi: None declared